2002
DOI: 10.1074/jbc.m109145200
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine and Celecoxib Lessen Cadmium Cytotoxicity Which Is Associated with Cyclooxygenase-2 Up-regulation in Mouse Neuronal Cells

Abstract: In many neurodegenerative disorders, aggregates of ubiquitinated proteins are detected in neuronal inclusions, but their role in neurodegeneration remains to be defined. To identify intracellular mechanisms associated with the appearance of ubiquitin-protein aggregates, mouse neuronal HT4 cells were treated with cadmium. This heavy metal is a potent cell poison that mediates oxidative stress and disrupts the ubiquitin/ proteasome pathway. In the current studies, the following intracellular events were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
34
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 40 publications
11
34
2
Order By: Relevance
“…19) Moreover, cadmium causes an increase in intracellular p53 protein levels and/or phosphorylated p53 protein levels in several cells. [57][58][59][60][61][62][63][64][65] These observations also support our findings that the p53-mediated pathway is one of the critical pathways for inducing apoptosis in chronic cadmium-exposed proximal tubular cells in the kidney.…”
Section: P53-dependent Pathwaysupporting
confidence: 79%
“…19) Moreover, cadmium causes an increase in intracellular p53 protein levels and/or phosphorylated p53 protein levels in several cells. [57][58][59][60][61][62][63][64][65] These observations also support our findings that the p53-mediated pathway is one of the critical pathways for inducing apoptosis in chronic cadmium-exposed proximal tubular cells in the kidney.…”
Section: P53-dependent Pathwaysupporting
confidence: 79%
“…Ubiquitinated proteins that are not degraded by the proteasome can accumulate and cause toxic cell damage. Previous studies have shown that Cd increases the accumulation of ubiquitinated proteins in several cell lines, such as mouse neuronal HT4 cells (Figueiredo-Pereira et al, 2002), rat sertoli cell-gonocyte cocultures (Yu et al, 2008) and rat proximal tubule cells (Thévenod and Friedmann, 1999). These findings suggest that Cd may cause toxic cell damage through the accumulation of unnecessary proteins.…”
mentioning
confidence: 55%
“…The proteasomal pathway is involved in COX-2 protein turnover (31)(32)(33)(34). This promptly led us to investigate whether the proteasomal pathway is associated with increased turnover of high molecular species of COX-2 by GS-HCl during translation.…”
Section: Gs-hcl Appears To Accelerate the Proteasome-dependent Degradmentioning
confidence: 99%